PURIFICATION AND CHARACTERIZATION OF RECOMBINANT Bacillus aquimaris MKSC 6.2 ?-AMYLASE EXPRESSED In Escherichia coli ArcticExpress (DE3) - Khaerunnisa Frima, Fina
?-Amylase (E.C 3.2.1.1) catalyzes the hydrolysis of internal ?-1,4-glycosidic linkages in starch. An ?-amylase from Bacillus aquimaris BaqA can degrade raw starch despite having no starch binding domain (SBD) which is commonly presence in the known raw starch degrading enzymes. BaqA is classified in a novel GH13 subfamily based on the presence of two consecutive tryptophans located at 201 and 202 position (W201 and W202) which are potential to play a role in starch binding. The first aim of this research was to study the function of two consecutive tryptophans W201 and W202. Secondly, this research also aimed to understand the propertises of BaqA wildtype.